Artificial feed capable of improving survival rate of larvae of beet armyworms - WU XIAOLIANG (2018)
The invention provides artificial feed capable of improving survival rate of larvae of beet armyworms. The artificial feed comprises the following main components: bran flour, soybean flour, feed-grade yeast powder, agar powder, sodium chloride, vitamin complex B, distillers' grains, citric acid, ferrous sulfate and water. The bran flour, the soybean flour and the distillers' grains are added on the basis of traditional feed, and the survival rate of the larvae of the beet armyworms is improved to 98% or higher. 本发明提供了种提高甜菜夜蛾幼虫成活率的人工饲料，包括以下主要成分：糠粉、大豆粉、饲料级酵母粉、琼脂粉、氯化钠、复合维生素B、酒糟、柠檬酸、硫酸亚铁和水，在传统的饲料的基础上加入了糠粉、大豆粉和酒糟，将甜菜夜蛾幼虫成活率提高到98%以上。